Microscopic Analysis of Bacterial Inoculum Effect Using Micropatterned Biochip - Jung Ho Hwang; Sang Young Lee; Jungil Choi (MDPI AG, 2021)
Antimicrobial resistance has become a major problem in public health and clinical environments. Against this background, antibiotic susceptibility testing (AST) has become necessary to cure diseases in an appropriate and timely manner as it indicates the necessary concentration of antibiotics. Recently, microfluidic based rapid AST methods using microscopic analysis have been shown to reduce the time needed for the determination of the proper antibiotics. However, owing to the inoculum effect, the accurate measurement of the minimal inhibitory concentration (MIC) is difficult. We tested four standard bacteria: Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Enterococcus faecalis, against five different antibiotics: piperacillin, cefotaxime, amikacin, levofloxacin, and ampicillin. The results showed that overall, the microfluidic system has a similar inoculum effect compared to the conventional AST method. However, due to the different testing conditions and determination protocols of the growth of the microfluidic based rapid AST, a few results are not identical to the conventional methods using optical density. This result suggests that microfluidic based rapid AST methods require further research on the inoculum effect for practical use in hospitals and can then be used for effective antibiotic prescriptions.